Urgent double balloon endoscopy provides higher yields than non-urgent double balloon endoscopy in overt obscure gastrointestinal bleeding - Aniwan, Satimai; Viriyautsahakul, Vichai; Rerknimitr, Rungsun; Angsuwatcharakon, Phonthep; Kongkam, Pradermchai; Treeprasertsuk, Sombat; Kullavanijaya, Pinit (Endoscopy International Open, 2014)
Background and study aims: In overt obscure gastrointestinal bleeding (OV), double balloon endoscopy (DBE) is recommended as one of the most important investigations as it can provide both diagnosis and treatment. However, there is no set standard on the timing of DBE in OV. The aim of this study was to compare the diagnostic and therapeutic yields between urgent and non-urgent DBE in patients with OV.Patients and methods: Between January 2006 and February 2013, 120 patients with OV who underwent DBE were retrospectively reviewed. An urgent DBE was defined as DBE performed within 72 h from the last visible gastrointestinal bleeding (n = 74) whereas a non-urgent DBE was defined as DBE performed after 72 h (n = 46). Diagnostic yields, therapeutic impact and clinical outcomes were evaluated.Results: Diagnostic yield in urgent DBE was significantly higher than that in non-urgent DBE (70 % versus 30 %; P < 0.05). Urgent DBE offered significantly more therapies including endoscopic, angiographic embolization, and surgery than non-urgent DBE (54 % versus 15 %; P < 0.001). Endoscopic therapy was performed in 43 % of urgent-DBE patients whereas only 13 % of patients in the other group received endoscopic therapy (P < 0.01). In patients with identified bleeding sources, the rebleeding rate was lower in patients who underwent urgent DBE than in those who underwent non-urgent DBE (10 % versus 29 %, NS).Conclusions: Regarding diagnostic and therapeutic impacts in OV, our retrospective study showed that urgent DBE is better than non-urgent DBE. The recurrent bleeding rate in patients undergoing urgent DBE tended to be lower.